FIP1L1-PDGFRA-Associated Hypereosinophilic Syndrome as a Treatable Cause of Watershed Infarction. Issue 10 (26th July 2021) - Tennenbaum, Juliette; Groh, Matthieu; Venditti, Laura; Campos-Gazeau, France; Chalayer, Emilie; De Broucker, Thomas; Hamidou, Mohamed; Hunault, Mathilde; Lyoubi, Aicha; Meunier, Raphaëlle; Muron, Thierry; Sène, Damien; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Ischemic stroke has been reported in various conditions associated with eosinophilia. FIP1L1-PDGFRA fusion ([Fip1-like 1-platelet-derived growth factor receptor alpha]; F/P ) leads to the proliferation of the eosinophilic lineage and thus to a clonal hypereosinophilic syndrome that is highly responsive to imatinib. Methods: We previously reported on a nationwide retrospective study of 151 patients with F/P -associated clonal hypereosinophilic syndrome. Patients from this cohort with a clinical history of ischemic stroke (as well as 2 additional cases) were further analyzed to better define their clinical picture and outcomes. Results: Sixteen male patients (median age, 51 [43–59] years) with low-to-intermediate cardiovascular risk were included. Median National Institutes of Health Stroke Scale was 4 (range, 1–6). Most cerebral imaging disclosed multiple bilateral infarctions of watershed distribution (69%). Despite frequent cardiac involvement (50%), cardiac thrombus was evidenced in a single patient and, according to the TOAST classification (Trial of ORG 10172 in Acute Stroke Treatment), 62.5% of strokes were presumably of undetermined etiology. Among the 15 patients treated with imatinib, and after a median follow-up of 4.5 years, stroke recurred in only 3 patients (consisting of either cardio embolic or hemorrhagic events, unrelated to the first episode). Conclusions: F/P + clonal hypereosinophilic syndrome is a diagnosis to consider in patients with unexplained ischemic stroke and hypereosinophilia (especially in the setting of multiple cortical borderzone distribution) and warrants prompt initiation of imatinib.